Exploring the Recurrence Risk Factors and Development of a Nomogram Prediction Model for Uterine Fibroid Patients Post-Myomectomy Based on Patient Medical Records - Li C; Li L; Hu Y (International Journal of Women's Health)
Caixia Li,1,* Liumin Li,1,* Yingchun Hu2 1Department of Gynecology, Xiaolan People’s Hospital of ZhongShan (The Fifth People’s Hospital of ZhongShan), Zhongshan City, Guangdong Province, 528415, People’s Republic of China; 2Department of Nursing Care, Xiaolan People’s Hospital of ZhongShan (The Fifth People’s Hospital of ZhongShan), Zhongshan City, Guangdong Province, 528415, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yingchun Hu, Email Jasmine59sci@163.comObjective: This study aims to investigate the risk factors contributing to the recurrence of uterine fibroids in patients undergoing laparoscopic myomectomy, providing a basis for clinical treatment.Methods: A retrospective analysis was conducted on 378 patients who underwent laparoscopic myomectomy between January 2022 and August 2023 and were subsequently followed up. Based on the recurrence status 6 months post-operation, patients were divided into a recurrence group (43 cases) and a non-recurrence group (335 cases). Clinical data of both groups were analyzed using univariate analysis, and factors statistically significant in univariate analysis were further evaluated through multivariate logistic regression to identify independent risk factors for recurrence post-laparoscopic myomectomy.Results: Univariate analysis indicated that the proportion of patients with ≥ 2 fibroids, intramural fibroids, and preoperative serum C-reactive protein (CRP) levels ≥ 4.67 mg/L was significantly higher in the recurrence group (all P< 0.05). Multivariate logistic regression analysis revealed that having ≥ 2 fibroids, a uterine size ≥ 14 gestational weeks, intramural fibroids, and preoperative serum CRP levels ≥ 4.67 mg/L were independent risk factors for recurrence post-laparoscopic myomectomy (OR=1.855, 1.038, 1.917, 1.208, 1.154, respectively; all P< 0.05).Conclusion: The presence of ≥ 2 fibroids, intramural fibroids, and preoperative serum CRP levels ≥ 4.67 mg/L are identified as independent risk factors for the recurrence of uterine fibroids post-laparoscopic myomectomy. Regular follow-ups should be conducted for patients with these risk factors to timely detect potential recurrence risks and implement preventive and therapeutic measures accordingly. The number of fibroids, their location, and preoperative serum CRP level have a strong predictive ability for recurrence after laparoscopic myomectomy, effectively identifying patients with recurrence while excluding those without recurrence.Keywords: uterine fibroids, laparoscopic myomectomy, recurrence, risk factors